2021
DOI: 10.3991/ijet.v16i23.27471
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Learning Analytics to Higher Education Institutions: A Scoping Review

Abstract: Learning analytics is a form of data analysis that allows teachers, lecturers, educational experts, and administrators of online learnings to look for students’ online traces and information associated with the learning processes. The fundamental goal of learning analytics in online classrooms and com-puter-supported instruction is to enhance the learning experience and the entire learning process. This review aims at reviewing some of the benefits available through using learning analytics in higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Main literature search was conducted on Taylor & Francis database (Kalogiannakis et al, 2021) via the National Library of the Republic of Indonesia. Search of articles from other publishers was also conducted on a widely used database in the education sector, ERIC (Education Resource Information Center) (Aydın & Gürol, 2019;Chalkiadaki, 2018;Diggs & Akos, 2016;Kalogiannakis et al, 2021;O'Flaherty & Liddy, 2018;Quadri & Shukor, 2021;Retuerto et al, 2020), involving excellent, peer-reviewed articles (Petticrew & Roberts, 2006;Torgerson, 2003). Based on ERIC database sources, we obtained articles from publishers International Council of Associations for Science Education, Australian Geography Teachers Association, International Society of Educational Research, Sciedu Press, Eastern Mediterranean University, and OmniaScience.…”
Section: Data Source Searchingmentioning
confidence: 99%
“…Main literature search was conducted on Taylor & Francis database (Kalogiannakis et al, 2021) via the National Library of the Republic of Indonesia. Search of articles from other publishers was also conducted on a widely used database in the education sector, ERIC (Education Resource Information Center) (Aydın & Gürol, 2019;Chalkiadaki, 2018;Diggs & Akos, 2016;Kalogiannakis et al, 2021;O'Flaherty & Liddy, 2018;Quadri & Shukor, 2021;Retuerto et al, 2020), involving excellent, peer-reviewed articles (Petticrew & Roberts, 2006;Torgerson, 2003). Based on ERIC database sources, we obtained articles from publishers International Council of Associations for Science Education, Australian Geography Teachers Association, International Society of Educational Research, Sciedu Press, Eastern Mediterranean University, and OmniaScience.…”
Section: Data Source Searchingmentioning
confidence: 99%
“…Module 1 of the proposed architecture is responsible for receiving data from the LMS and storing them in a repository of learning records. In this module an Endpoint for queries in SPARQL language 4 was implemented, which allows communication with Module 2 (Processing Unit and Analytics). To this end, an open source Learning Record Store (LRS) Learning Locker, 5 made available by HT2 Labs and which we integrate with the semantic data query service through the Apache Jena Fuseki framework.…”
Section: Artifact Iii: Sapes Toolmentioning
confidence: 99%
“…As stated, LA allows a source of educational data from a virtual learning environment. According to Quadrii and Shukor [4], LA is gaining strength in educational institutions for positively impacting the teaching and learning process in e-Learning. Also, Husni et al [36] indicated that the planning of didactic-pedagogical actions based on the educational information inferred from LA helps educational professionals to appropriately design pedagogical strategies.…”
Section: Even Though I'm Carrying Out the Activities In The Virtual E...mentioning
confidence: 99%
See 2 more Smart Citations